Modelbuilding : basics. - Schilling, Alexander, ....- (Basel : Birkhäuser, 2007)
Models make it possible to visualize an idea in three dimensions. Designing with models and presenting ideas is an important step in the development of a consciousness of design. Themes: Levels of abstraction and degrees of detail Model typologies Typical working tools and techniques Materiality of models Presentation possibilities
Keywords: Modelbouw ; architectuur